Prophylactic and therapeutic potential of active phytoconstituents from Amomum subulatum Roxb. Issue 1 (23rd November 2022) - Dhakal, Richa; Dihingia, Anjum; Ahmed, Ruksana Sultana; Gupta, Dipanneeta Das; Sahu, Ravi Kumar; Dutta, Prachurjya; Bharali, Pankaj; Manna, Prasenjit; Sastry, G. Narahari; Kalita, Jatin
Abstract: Amomum subulatum is a popular aromatic and medicinal spice crop being used for centuries to treat a variety of health ailments. The ethnopharmacological use of Amomum subulatum has been described in various medicinal systems including Ayurveda, Unani, and Chinese for its therapeutic properties in mitigating gastrointestinal disorders, lung congestions, respiratory ailments, jaundice, tuberculosis, hyperlipidemia, inflammation, ischemic heart diseases, etc. Literature search using Google Scholar, PubMed, NCBI, Elsevier, Wiley online Library, Springer, Taylor and Francis, Web of Science, Science Direct, Scopus databases was restricted to English‐language articles. Significant information on pharmacological properties of Amomum subulatum, including antioxidant (ROS/RNS pathways), anti‐inflammatory (TNF‐α, IL‐1, IL‐6, COX‐2, NF‐кB, HO‐1, arachidonic acid pathways), antinephrotoxic (urea, creatinine, Cystatin‐C), antihepatotoxic (SGOT, SGPT, and ALP), antidiabetic, etc., was collected for the review. The pharmacological properties of this traditional herb may be attributed to the plethora of secondary metabolites present in it. Preliminary phytochemical screening reported the abundance of flavonoids, terpenoids, steroids, vitamins, minerals, fatty acid esters, etc. 1, 8‐cineole (60%–80% of total volatile oil), α‐terpineol, limonene, α‐terpinyl acetate, etc., are the notable phytochemicals reported from Amomum subulatum . However, detailed insights into the molecular mechanistic pathways mediating the beneficial role of this traditional herb on cell/animal models and large‐scale clinical trials are lacking. In the present review, we provide a comprehensive description of the current knowledge on Amomum subulatum, including its phytoconstituents, pharmacological uses, and toxicities, its implication in host health effects, including in vitro/in vivo efficacy, and the potential of these emerging species to suggest areas for future research.